Pembinaan Narapidana Perempuan dalam Perspektif Hukum di Lapas Kelas III Gorontalo - lahabu, Fatma Lahabu; HR, Muhammad Adam (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
The main objective of the Correctional System in Indonesia is to rehabilitate inmates into fully developed individuals who are able to improve themselves, acknowledge their mistakes, and refrain from repeating criminal offenses. Ultimately, this process aims to reintegrate them into society, enabling them to actively participate in development and live as responsible, law-abiding citizens. Correctional Institutions (Lapas) serve as rehabilitation centers for inmates and juvenile offenders. Therefore, inmates are required to participate in all available rehabilitation programs, including the Self-Reliance Development Program. This program consists of two main components: Skills Training and the Production of Goods/Services. This research focuses on the implementation of the Self-Reliance Development Program for inmates, as well as the challenges encountered, particularly those related to human resources and the availability of facilities and infrastructure. This study uses a sociological approach and falls under the category of empirical legal research, in which the researcher conducted fieldwork to gather data. Primary data were obtained through documentation, interviews, and observation, while secondary data were sourced from literature relevant to the research topic. The findings show that the Women’s Correctional Institution Class III Gorontalo has implemented the Self-Reliance Development Program for inmates in accordance with the objectives of the Correctional System as mandated by the prevailing laws and regulations. However, its implementation still faces several obstacles, particularly in terms of human resources and the supporting facilities and infrastructure required for the program.